Atmospheric Photo-Oxidation of Acetic Anhydride: Kinetic Study and Reaction Mechanism. Products Distribution and Fate of Ch3c(O)Oc(O)Ch2o·Radical - Vila, Jesús A.; Rimondino, Guido N.; Peláez, Walter J.; Kalinowski, Mateo; Malanca, Fabio E. (2024)
This is a preprint article, it offers immediate access but has not been peer reviewed.